LANGUAGE MODE: A CONVERSATIONAL ANALYSIS ON THE LANGUAGE USE OF FILIPINO BILINGUALS - Jose, Eunice B; Quinain, Mary Robin P.; Constantino, Christy Tan (Universitas Muhammadiyah Surakarta, 2019)
This study, using a quantitative-qualitative research design, aimed to determine and analyze the language mode of Filipino bilinguals from the University of San Carlos ? Talamban Campus Cebu, Philippines. Specifically, this study focused on the language use in conversational strategies and the factors that influenced their language mode. The data were taken from seven small group conversations consisting of three bilinguals each. The data gathering involved a brief survey, a picture-stimuli to elicit conversations, and an interview. Findings revealed that when the bilinguals activated both of their languages in utilizing strategies, Code Switching, Filler, and Surprising were the top three conversational strategies that were mostly used. Also, results revealed that the language mode of bilinguals were largely-dependent on the Participants and Situation of the interaction. Moreover, another notable finding was that the bilinguals were always in their bilingual language mode as evident in their utilization of the CSs in their available languages. These outcomes suggest that even if bilingualism intervenes lexical retrieval in both languages, it still improves and ensures the flow of the communication process; hence, it does not adversely affect the usage of the first language. Keywords: bilingualism, language mode, Filipino bilingual, conversational analysis, conversational strategies